Nows, Thens, and Truths: Attending to the Present in Performing the Past - Impett, Jonathan (New York Oxford University Press, 2024)
This chapter has two modest points to make. First, that the very notion of ‘early music’ tendsto distract its practitioners from the need to engage critically with the present, and that suchengagement is complicated precisely by its historical positioning. And second – morespeculatively, perhaps – that ours is a moment of epochal re-orientation in terms of globalhistory and cultures, and that this presents both challenges and opportunities for the currentpractices of early music.
FRIS
Editorial review
Keywords: Music, Thought and Technology